2008
DOI: 10.1002/iroh.200711019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream

Abstract: This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of -0.0332, -0.0108, and -0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
2
24
0
3
Order By: Relevance
“…), and Spanish oak (Quercus ilex ilex L.). Common alder and sweet chestnut are deciduous trees, and in previous studies in Portuguese streams have shown fast and medium breakdown rates, respectively (ABELHO and GRAÇA, 1996;CANHOTO and GRAÇA, 1996;ABELHO, 2008). Spanish oak is an evergreen sclerophyllous tree typical from the Mediterranean chaparral and, although it is not a riparian tree, was chosen due to its leaf toughness and slow breakdown rate (ABELHO, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…), and Spanish oak (Quercus ilex ilex L.). Common alder and sweet chestnut are deciduous trees, and in previous studies in Portuguese streams have shown fast and medium breakdown rates, respectively (ABELHO and GRAÇA, 1996;CANHOTO and GRAÇA, 1996;ABELHO, 2008). Spanish oak is an evergreen sclerophyllous tree typical from the Mediterranean chaparral and, although it is not a riparian tree, was chosen due to its leaf toughness and slow breakdown rate (ABELHO, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Specific elements can show different release patterns in different types of litter (Jonczak et al 2014). Moreover, litter species can affect the microbial and invertebrate assemblages in rivers and thus exert indirect effects on litter decomposition and element release (Leroy and Marks 2006;Abelho 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that leaf litter of different plant species is colonized by different invertebrates (Junke and Trivinho-Strixino, 2007;Abelho, 2008) and also presented data reinforcing that shredder invertebrates are able to discriminate among leaf types (Abelho, 2001;Graça, 2001). Thus, the structure of riparian vegetation will determine the nature of the allochthonous matter entering the aquatic environment, which in turn could have an influence on the structure of the aquatic invertebrate assemblages.…”
Section: Introductionmentioning
confidence: 59%
“…Although it has lower physical stability than rock substrate, leaf litter of allochthonous origin also has an important role in the structuring of stream invertebrate community (Uieda and Motta, 2007), enabling litter colonization by a high density and diversity of organisms (Gonçalves Junior et al, 2006a, b;Crisci-Bispo et al, 2007;Junke and Trivinho-Strixino, 2007;Moretti et al, 2007;Abelho, 2008;Carvalho et al, 2008;Schindler and Gessner, 2009). This material of allochthonous origin is fundamental for energy flow and carbon stocks of low-order streams with riparian vegetation (Vannotte et al, 1980;Wallace et al, 1997), and its decomposition constitutes a key process in the structure and metabolism of river systems (Cummins, 1988).…”
Section: Introductionmentioning
confidence: 99%